2015
DOI: 10.1007/s00122-015-2614-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study, genomic prediction and marker-assisted selection for seed weight in soybean (Glycine max)

Abstract: Key messageTwenty-two loci for soybean SW and candidate genes conditioning seed development were identified; and prediction accuracies of GS and MAS were estimated through cross-validation and validation with unrelated populations.AbstractSoybean (Glycine max) is a major crop for plant protein and oil production, and seed weight (SW) is important for yield and quality in food/vegetable uses of soybean. However, our knowledge of genes controlling SW remains limited. To better understand the molecular mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
164
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(182 citation statements)
references
References 60 publications
3
164
3
2
Order By: Relevance
“…This type of panel is expected to exhibit a greater genetic diversity than panels constituted of lines from breeding programs. Zhang et al (2016) confirmed that seed weight was under the influence of many minor-effect loci in their panel, and they obtained an equivalent prediction accuracy using 2000 or 31,045 SNPs.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…This type of panel is expected to exhibit a greater genetic diversity than panels constituted of lines from breeding programs. Zhang et al (2016) confirmed that seed weight was under the influence of many minor-effect loci in their panel, and they obtained an equivalent prediction accuracy using 2000 or 31,045 SNPs.…”
Section: Discussionsupporting
confidence: 52%
“…Jarquín et al (2014) reported robustness of prediction accuracy for yield when using different sets of markers in a panel of experimental lines from a breeding program. Zhang et al (2016) reported results from association analyses and assessment of genomic prediction accuracy for seed weight, a component trait of yield, in a panel of accessions from the USDA germplasm collection. This type of panel is expected to exhibit a greater genetic diversity than panels constituted of lines from breeding programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The objective of genomic selection is to identify possible markers in linkage disequilibrium with the gene regions of interest. Since this pioneering study, several authors have used this technique to predict the genetic value in several plant species, such as corn (Beyene et al, 2015), soybeans (Zhang et al, 2016), wheat (Bassi et al, 2016), forest species (Cros et al, 2015), sugarcane (Gouy et al, 2013), and rice (Spindel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%